2018 IEEE International Conference on Software Architecture (ICSA) 2018
DOI: 10.1109/icsa.2018.00014
|View full text |Cite
|
Sign up to set email alerts
|

Towards Micro Service Architecture Recovery: An Empirical Study

Abstract: Micro service architectures are rapidly establishing themselves in the software industry as a more efficient and effective substitute for monolithic applications. In a micro service architecture, the application is broken down into many small elements called micro services. These are managed in a distributed way and typically involve several development teams. In such an environment, an architectural model can get lost along the way, making it difficult to perform many downstream software engineering tasks, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…Some studies mainly focus on modeling microservices. 205,206 Their focus partially overlaps with our following research question: what are the modeling approaches used to define the granularity of a microservice?…”
Section: Related Studiesmentioning
confidence: 99%
“…Some studies mainly focus on modeling microservices. 205,206 Their focus partially overlaps with our following research question: what are the modeling approaches used to define the granularity of a microservice?…”
Section: Related Studiesmentioning
confidence: 99%
“…Using deployment artifacts for containers, particularly Docker Compose files and build scripts, support identifying the architecture of a microservice system [134]. It can identify remote endpoints and services and dependencies.…”
Section: Deployment / Build Configuration Analysismentioning
confidence: 99%
“…Two secondary studies [1,8] have reported a possible lack of research in architecture recovery techniques specific for MSA. Two different approaches have been published so far: MicroART [15] and MiSAR [2]. MicroART is an approach for automatic architecture recovery of MSA systems and leverages its own specific domain-specific language using Model Driven Engineering techniques.…”
Section: Related Workmentioning
confidence: 99%
“…MicroART is an approach for automatic architecture recovery of MSA systems and leverages its own specific domain-specific language using Model Driven Engineering techniques. MiSAR [2] is a more recent approach for architecture recovery and relies on a different set of concepts mapped on its own specific metamodel. An important difference between the two approaches is that while MicroART is automatic, MiSAR relies on a manual process for the definition of mapping rules as well as for the code inspection.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation